2020
DOI: 10.1515/biol-2020-0006
|View full text |Cite
|
Sign up to set email alerts
|

Morphine modulates hippocampal neurogenesis and contextual memory extinction via miR-34c/Notch1 pathway in male ICR mice

Abstract: AbstractBackgroundThe opioid Morphine is known to affect neurogenesis in the hippocampus. Evidence has shown that several microRNAs modulate morphine-induced neurogenesis, and hence morphine-induced contextual memory. This complex network has yet to be elucidated. In this study, we screened for morphine addiction related microRNA and determined its effects on hippocampal neurogenesis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…In recent years, neuroscience and behavioral science research of drug addiction have made many progress [ 1 , 2 ]. Although its complex mechanism of action is not yet clear, many studies have shown that drug addiction is a chronic and recurrent encephalopathy and its root cause is addictive memory [ 3 , 4 ].…”
Section: Introductionsmentioning
confidence: 99%
“…In recent years, neuroscience and behavioral science research of drug addiction have made many progress [ 1 , 2 ]. Although its complex mechanism of action is not yet clear, many studies have shown that drug addiction is a chronic and recurrent encephalopathy and its root cause is addictive memory [ 3 , 4 ].…”
Section: Introductionsmentioning
confidence: 99%